2019
DOI: 10.1371/journal.pone.0221688
|View full text |Cite
|
Sign up to set email alerts
|

What works best for ensuring treatment adherence. Lessons from a social support program for people treated for tuberculosis in Ukraine

Abstract: Background Worldwide, TB is one of the top 10 causes of death and the leading cause from a single infectious agent. Ukraine is one of 30 countries with the highest burden of multidrug-resistant tuberculosis. Global literature shows that social support (SS) is important in improving TB treatment adherence, reducing lost to follow up rates and improving treatment outcomes. There are several models of SS available, and the literature provides little information on what aspects of SS are most importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 8 publications
1
23
0
3
Order By: Relevance
“…These challenges emerged as factors that undermine treatment adherence and are consistent with identified adherence barriers in other sociopolitical contexts, thus suggesting that interventions implemented successfully elsewhere would be appropriate for consideration in Ukraine. A recent qualitative study among patients with TB in Ukraine similarly identified the inconvenience and cost of clinic-based DOT during the ambulatory phase of treatment as major challenges to treatment adherence 31. Our study provides additional insights into how hospitalisation and patient interactions with TB providers adversely influence adherence in the context of TB services in Ukraine.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…These challenges emerged as factors that undermine treatment adherence and are consistent with identified adherence barriers in other sociopolitical contexts, thus suggesting that interventions implemented successfully elsewhere would be appropriate for consideration in Ukraine. A recent qualitative study among patients with TB in Ukraine similarly identified the inconvenience and cost of clinic-based DOT during the ambulatory phase of treatment as major challenges to treatment adherence 31. Our study provides additional insights into how hospitalisation and patient interactions with TB providers adversely influence adherence in the context of TB services in Ukraine.…”
Section: Discussionmentioning
confidence: 65%
“…A prior analysis of UNTP has concluded that hospital-based TB care contributes to poor outcomes,30 and the latest UNTP guidelines recommend outpatient management of DSTB 12. Moreover, a pilot study in Ukraine recently reported home-based DOT facilitated retention in TB care 31. Ongoing reorganisation of TB care in Ukraine will provide opportunities to assess how full-scale implementation of home-based DSTB treatment influences patients’ experiences and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations